Increased Frequencies of Th22 Cells as well as Th17 Cells in the Peripheral Blood of Patients with Ankylosing Spondylitis and Rheumatoid Arthritis - Zhang, Lei; Li, Yong-gang; Li, Yu-hua; Qi, Lei; Liu, Xin-guang; Yuan, Cun-zhong; Hu, Nai-wen; Ma, Dao-xin; Li, Zhen-feng; Yang, Qiang; Li, Wei; Li, Jian-min (PLOS ONE, 2012)
Background T-helper (Th) 22 is involved in the pathogenesis of inflammatory diseases. The roles of Th22 cells in the pathophysiological of ankylosing spondylitis (AS) and rheumatoid arthritis (RA) remain unsettled. So we examined the frequencies of Th22 cells, Th17 cells and Th1 cells in peripheral blood (PB) from patients with AS and patients with RA compared with both healthy controls as well as patients with osteoarthritis. Design and Methods We studied 32 AS patients, 20 RA patients, 10 OA patients and 20 healthy controls. The expression of IL-22, IL-17 and IFN-γ were examined in AS, RA, OA patients and healthy controls by flow cytometry. Plasma IL-22 and IL-17 levels were examined by enzyme-linked immunosorbent assay. Results Th22 cells, Th17 cells and interleukin-22 were significantly elevated in AS and RA patients compared with OA patients and healthy controls. Moreover, Th22 cells showed positive correlation with Th17 cells as well as interleukin-22 in AS and RA patients. However, positive correlation between IL-22 and Th17 cells was only found in AS patients not in RA patients. In addition, the percentages of both Th22 cells and Th17 cells correlated positively with disease activity only in RA patients not in AS patients. Conclusions The frequencies of both Th22 cells and Th17 cells were elevated in PB from patients with AS and patients with RA. These findings suggest that Th22 cells and Th17 cells may be implicated in the pathogenesis of AS and RA, and Th22 cells and Th17 cells may be reasonable cellular targets for therapeutic intervention.